CHARACTERISTICS OF ACUTE ISCHEMIC STROKE PATIENTS DUE TO SMALL VESSEL OCCLUSION - Richard Suherlim; Nyoman Angga Krishna Pramana; Kumara Tini; Ida Bagus Kusuma Putra; Ida Ayu Sri Indrayani (MNJ (Malang Neurology Journal), 2023)
Background: Ischemic stroke account for about 87% of all stroke cases. This study will focus on ischemic stroke due to small vessel occlusion as one of the subtypes based on TOAST (trial of ORG 10172 in acute stroke treatment). Objective: To determine the characteristics of ischemic stroke patients caused by small vessel occlusion and are expected to be used as a basis for further research. Methods: A descriptive observational retrospective study regarding the characteristics of acute ischemic stroke patients due to small vessel occlusion at Sanglah Hospital. Secondary data were obtained from patient medical records. Results: The total number of cases of small vessel occlusion was 338. The majority of the sample were men (64.5%) between 40-60 years old (53.6%). Most of the samples were patients who had experienced an ischemic stroke for the first time (75.1%) with NIHSS (National Institute of Health Stroke Scale) scores showing mild (48.2%) and moderate (51.5%) symptoms. Around half of them had a history of hypertension (60.1%), dyslipidemia (59.5%), and diabetes mellitus (44.1%). The most common location of infarction was in the anterior circulation (77.5%) with almost the same ratio of right and left hemisphere locations. Conclusion: Ischemic stroke due to occlusion of small vessels at Sanglah Hospital Denpasar for 3 years was 35.2% of the total ischemic stroke cases. Half of the total sample had classic vascular risk factors. Further research is needed to determine another effective treatment strategy other than just secondary prevention such as life style moderation to prevent recurrency.